(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aims to determine the protein profile based on molecular weight (MW) and testosterone levels in seminal plasma (SP) that correlates to the semen quality of candidate Madura bulls. Material and Methods: A total of 10 male candidate madura bulls underwent semen evaluation (motility, viability, membrane plasma integrity (MPI), and sperm concentration). The centrifuge was run at 1,200 rpm (4°C) for 20 min to collect SP. SP testosterone levels were measured using an Enzyme-linked immunosorbent assay. The characterization of SP proteins in Madura bulls was done using 1D sodium dodecyl-sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. All parameters were analyzed using Pearson correlation analysis. Result: The results of the SDS-PAGE analysis found eight protein bands with the highest MW of 110 kDa and the lowest of 12 kDa. The mean and SD of SP testosterone levels were 20.58 ± 8.56 ng/ml, motility 59.32% ± 20.14%, viability 67.45% ± 20.22%, MPI 32.77% ± 16.52%, and sperm concentration 1,002.64 ± 429.33 106 /mm3. Proteins with MWs of 110 and 91 kDa significantly correlated with MPI, and 110 kDa negatively correlated with sperm concentration (p < 0.05). Proteins with MWs of 73 and 36 kDa significantly correlated with SP testosterone levels, while proteins with MWs of 29 kDa significantly correlated with sperm viability (p < 0.05). Conclusion: The expressed protein fraction based on MW is closely related to the quality of semen, so it has the potential to be a biomarker of semen quality. Further research is needed to determine the specific proteins in certain fractions. J. Adv. Vet. Anim. Res., 10(3): 429–436, September 2023 http://doi.org/10.5455/javar.2023.j696